Early tropical crop production in marginal subtropical and temperate Polynesia - Prebble, Matthew (Proc Natl Acad Sci U S A, 2019)
Polynesians introduced the tropical crop taro (Colocasia esculenta) to temperate New Zealand after 1280 CE, but evidence for its cultivation is limited. This contrasts with the abundant evidence for big game hunting, raising longstanding questions of the initial economic and ecological importance of crop production. Here we compare fossil data from wetland sedimentary deposits indicative of taro and leaf vegetable (including Sonchus and Rorippa spp.) cultivation from Ahuahu, a northern New Zealand offshore island, with Raivavae and Rapa, both subtropical islands in French Polynesia. Preservation of taro pollen on all islands between 1300 CE and 1550 CE indicates perennial cultivation over multiple growing seasons, as plants rarely flower when frequently harvested. The pollen cooccurs with previously undetected fossil remains of extinct trees, as well as many weeds and commensal invertebrates common to tropical Polynesian gardens. Sedimentary charcoal and charred plant remains show that fire use rapidly reduced forest cover, particularly on Ahuahu. Fires were less frequent by 1500 CE on all islands as forest cover diminished, and short-lived plants increased, indicating higher-intensity production. The northern offshore islands of New Zealand were likely preferred sites for early gardens where taro production was briefly attempted, before being supplanted by sweet potato (Ipomoea batatas), a more temperate climate-adapted crop, which was later established in large-scale cultivation systems on the mainland after 1500 CE.